Accelerated Ripening in Chemically Fueled Emulsions. Issue 2 (15th October 2020) - Tena‐Solsona, Marta; Janssen, Jacqueline; Wanzke, Caren; Schnitter, Fabian; Park, Hansol; Rieß, Benedikt; Gibbs, Julianne M.; Weber, Christoph A.; Boekhoven, Job
Abstract: Chemically fueled emulsions are solutions with droplets made of phase‐separated molecules that are activated and deactivated by a chemical reaction cycle. These emulsions play a crucial role in biology as a class of membrane‐less organelles. Moreover, theoretical studies show that droplets in these emulsions can evolve to the same size or spontaneously self‐divide when fuel is abundant. All of these exciting properties, i. e ., emergence, decay, collective behavior, and self‐division, are pivotal to the functioning of life. However, these theoretical predictions lack experimental systems to test them quantitively. Here, we describe the synthesis of synthetic emulsions formed by a fuel‐driven chemical cycle, and we find a surprising new behavior, i. e ., the dynamics of droplet growth is regulated by the kinetics of the fuel‐driven reaction cycle. Consequently, the average volume of these droplets grows orders of magnitude faster compared to Ostwald ripening. Combining experiments and theory, we elucidate the underlying mechanism. Abstract : Chemically fueled emulsions are solutions with droplets made of phase‐separated molecules activated and deactivated by a chemically‐fueled reaction cycle. Such systems are present in biology, but synthetic analogues are limited. Here, we describe human‐made chemically fueled emulsions, and we find a surprising behavior,   i.e .,  the dynamics of droplet growth is regulated by the kinetics of the fuel‐driven reaction cycle. Combining experiments and theory, we elucidate the underlying mechanism, which relies on the acceleration of Ostwald ripening.